2022
DOI: 10.1002/jbt.23024
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of rotenone‐induced alterations in energy/redox system, stress response and cytoskeleton proteins by octanoic acid in zebrafish: A proteomic study

Abstract: Rotenone is used to generate Parkinson's disease (PD)-like symptoms in experimental animals. Octanoic acid (C8), is the principal fatty acid of medium-chain triglycerides in ketogenic diets. Beneficial effects of ketogenic diets were shown in PD. We applied proteomic methods to reveal the effects of octanoic acid in rotenone toxicity in zebrafish to gain information on the use of ketogenic diets in PD. Zebrafish were exposed to 5 μg/ml rotenone and octanoic acid (20 and 60 mg/ml) for 30 days. LC-MS/MS analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…This imbalance has also been identified as a key contributor to busulfan-induced reproductive toxicity [ 34 ]. Accumulating in vitro and in vivo evidence has elucidated the multifaceted mechanisms by which OCA ameliorates various diseases, notably through the alleviation of oxidative stress [ 20 , 35 ]. In this study, OCA treatment effectively improved busulfan-induced oxidative stress in the testes.…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance has also been identified as a key contributor to busulfan-induced reproductive toxicity [ 34 ]. Accumulating in vitro and in vivo evidence has elucidated the multifaceted mechanisms by which OCA ameliorates various diseases, notably through the alleviation of oxidative stress [ 20 , 35 ]. In this study, OCA treatment effectively improved busulfan-induced oxidative stress in the testes.…”
Section: Discussionmentioning
confidence: 99%
“…As the main fatty acid component of medium chain triglycerides in ketogenic diet, OA directly enters the liver through the portal vein, after being absorbed by the human body, bypassing the lymphatic system. NAD + /NADH could be improved by liver mitochondria to reduce metabolic dysfunction (26). Studies have shown that a diet rich in OA could increase the number of mitochondria and provide more energy for the body (27).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the samples were centrifuged at 1000×g and the flow through were collected. The digestion protocol applied to obtain the tryptic peptide was similar to our previous study (8). An equal amount of protein for each sample was reduced with 20 mM DTT for 10 min at 95°C and then alkylated with 40 mM iodoacetamide for 20 min in the dark.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The peptide mixtures were separated by a reverse phase nano-flow liquid chromatography (Dionex UltiMate 3000, Thermo Fisher Scientific) and identified using high resolution mass spectrometry (Q-Exactive Plus Orbitrap, Thermo Fisher Scientific) equipped with an electrospray ionization source. The analyses were performed by selecting the previous nano-UPLC-ESI-MS/MS system parameters (8). For analysis, each sample was re-dissolved in 0.1% formic acid and then loaded onto a trap column.…”
Section: Lc-ms/ms Analysis and Data Processingmentioning
confidence: 99%